DESIGNING THE HORIZONTAL AXIS SHROUDED RIVER CURRENT TURBINE FOR THE EXPERIMENTAL PURPOSE IN HALU OLEO UNIVERSITY - Aditya Rachman (Dinamika : Jurnal Ilmiah Teknik Mesin, 2015)
The clean renewable energy technology development should be on the top government program priority in present day, as the current energy availability and environmental challenges over the majority in the use of the unclean conventional power technologies. University has potential role to support the clean renewable energy development through research activities. This study deals with designing the clean renewable power technology based on a horizontal axis shrouded river current for experimental purpose in Halu Oleo University Indonesia. To fulfill this objective, some parts on the turbine unit are designed to be adjustable, thus, possibly making the process for the experiment. The method utilized in this study is the combination of literature review, mathematical model use, design and manufacture on the turbine. The result of this study is a unit of the horizontal axis shrouded river current turbine in which some of its parts, such as the shrouding device and the blade angle, are adjustable for the experimental purpose.